2016
DOI: 10.3389/fphys.2016.00384
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Baroreceptors Display Higher Mechanosensitivity than Carotid Baroreceptors

Abstract: Arterial baroreceptors are mechanical sensors that detect blood pressure changes. It has long been suggested that the two arterial baroreceptors, aortic and carotid baroreceptors, have different pressure sensitivities. However, there is no consensus as to which of the arterial baroreceptors are more sensitive to changes in blood pressure. In the present study, we employed independent methods to compare the pressure sensitivity of the two arterial baroreceptors. Firstly, pressure-activated action potential firi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…10 Aortic arterial baroreceptors are likely the "first responders," as they are activated at slightly lower pressure thresholds. 11 Low-pressure baroreceptors in the myocardium, pulmonary veins, and coronary circulation are distinct receptor types activated by specific stimuli 12 but are collectively termed cardiopulmonary baroreceptors. They control vascular resistance to mostly skeletal muscle, 10 renal sympathetic outflow, 13 sodium/water balance, 14 and renin release, 15 but they have only a minimal effect on heart rate.…”
Section: Afferent Baroreceptor Signalsmentioning
confidence: 99%
“…10 Aortic arterial baroreceptors are likely the "first responders," as they are activated at slightly lower pressure thresholds. 11 Low-pressure baroreceptors in the myocardium, pulmonary veins, and coronary circulation are distinct receptor types activated by specific stimuli 12 but are collectively termed cardiopulmonary baroreceptors. They control vascular resistance to mostly skeletal muscle, 10 renal sympathetic outflow, 13 sodium/water balance, 14 and renin release, 15 but they have only a minimal effect on heart rate.…”
Section: Afferent Baroreceptor Signalsmentioning
confidence: 99%
“…This is intriguing given that arterial baroreceptors are located at both sites. Previous studies have suggested that the aortic baroreflex is more important than the carotid baroreflex in blood pressure regulation in young men (26) and that aortic baroreceptors have a higher pressure mechanosensitivity than carotid baroreceptors (15). In addition, the aortic baroreflex in isolation can produce a sustained inhibition of MSNA, whereas the carotid baroreflex cannot achieve this (26).…”
Section: Impact Of Barosensory Vessel Unloading Mechanics On Baroreflex Function In Young Menmentioning
confidence: 95%
“…As regards functional comparison between carotid and aortic baroreceptors, conflicting results are found in the literature: some authors report higher sensitivity for carotid baroreceptors (Donald and Edis, ; Fadel et al, ), some for aortic baroreceptors (Pickering et al, ; Lau et al, ) and others do not report any significant differences (Hainsworth et al, ; James and Daly, ).…”
Section: Targets Of the Csnmentioning
confidence: 99%